Tuberous Sclerosis: Diagnostic Criteria - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The Diagnostic Criteria Committee of the National Tuberous Sclerosis Association reports primary, secondary, and tertiary features of the disease complex and considers the specificity and reliability of the various lesions.